5, 5-Dioxoyphenothiazine-based D-A-D type AIE molecules enabling persistent room temperature phosphorescence, white light emission and dual-mode mechanochromism. (April 2021) - Zhou, Xiaolu; Xu, Songlin; Liu, Liqiang; Sun, Yiping; Cheng, Jinxi; Duan, Xingyu; Zhou, Lishan; Qu, Hongmei
Abstract: Novel heavy atom free 5, 5-dioxoyphenothiazine-based "D–A–D" emitters with aggregation-induced emission (AIE), room-temperature phosphorescence (RTP), white light emission and dual-mode mechanochromic luminescence (MCL) characteristics have been designed and synthesized. Impressively, DCzCs and DCzCs-Et showed persistent RTP (pRTP) in the crystalline state with lifetimes of 528 ms and 137 ms in air, respectively. DCzCs-Ac exhibited white light emission with a CIE coordinate of (0.25, 0.26), due to the dual emission of fluorescence and phosphorescence. Detailed studies have shown that through simply functional group modification on the acceptor skeleton to modulate the molecular structure and intermolecular interactions, we fine-tuned the optical properties of the luminogens and realized white light emission. The dense crystal packing was proved to be closely related to the phosphorescence of the system and the special dual-mode MCL behavior was attributed to the conversion of crystalline-amorphous state under external force. Graphical abstract: Image 1 Highlights: Three 5, 5-Dioxoyphenothiazine-based D-A-D type derivatives were synthesized. Phosphorescence features of luminogens were fine-tuned by functional group modification on acceptor. These luminogens exhibited obvious aggregation-induced emission and dual-mode mechanochromism characteristics. Luminogen DCzCs-Ac exhibited obvious white emission.